PERSEPSI GURU SEKOLAH DASAR TERHADAP PERMENDIKBUDRISTEK NOMOR 46 TAHUN 2023 TENTANG PENCEGAHAN DAN PENANGANAN KEKERASAN - Sauri, R Supyan; Khoirudin, Asmi; Rusmiati, Esih; Jalil, Dani Muhammad; Wulansari, Destianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Bullying in elementary schools is a serious problem that threatens student welfare and disrupts the learning process. In response to this condition, the Indonesian government issued Minister of Education, Culture, Research and Technology Regulation Number 46 of 2023 concerning Prevention and Handling of Violence in Educational Units. This study aims to analyze elementary school teachers' perceptions of the policy, identify teachers' level of understanding, and describe the implementation of the Violence Prevention and Handling Team (TPPK) at the educational unit level. The study employed a qualitative approach with a single case study design focusing on phenomenology, conducted at SDN Suryalaya 202 Bandung City in October-November 2025. Research subjects were three classroom teachers selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and documentation studies, then analyzed using thematic analysis model. The results show that teachers have a basic understanding of the policy although with varying levels, perceiving the policy as an important legal umbrella and operational guideline. TPPK implementation is still in its early phase with various socialization efforts requiring more structured systematization. The policy has a positive impact on teacher-student interactions and increases awareness of the importance of multi-party collaboration in preventing violence in schools